ANALISIS KETERPAKAIAN REFERENSI: STUDI KASUS LAPORAN AKHIR RISET KOMPETITIF LIPI 2003 – 2007 BIDANG KALIMANTAN TIMUR & BANGKA BELITUNG, PRODUK KOMODITAS & TEKNOLOGI, DAN WILAYAH PERBATASAN NTT - Nani Rahayu, Rochani; Tupan, Tupan; Mardiana, Mardiana (BACA: Jurnal Dokumentasi dan Informasi, 2012)
Study of reference usage analysis on final report of LIPI‘s Competitive Research (2003 -2007) has some goals, i.e to find out: kinds and sources of document which were cited, also median half life of document used by researchers as references. This research focused on 3 fields of research areas, i.e: East Kalimantan and Bangka Belitung (EKBB), Product, Comodities, and Technology (PCT), and Border Region of East Nusa Tenggara (BRENT). Data was obtained by recording the research titles and all of the references used by researchers on the final research reports. All recorded data including information resources, such as books, journals, proceedings, thesis, etc, then tabulated, grouped, and presented on tables. The results show that total citation in the area of: EKBB, PCT, and BRENT are 580, 260, and 147 respectively. The most citation is coming from foreign literatures. The author also found that many researchers still did not write down their references carefully, for examples no publication date and no access date (for internet sources). Median half life for all the research fields is ≥ 10 years.